Effect of Virtual Monoenergetic Images From Spectral Detector Computed Tomography on Coronary Calcium Blooming. Issue 6 (November 2018) - Van Hedent, Steven; Große Hokamp, Nils; Kessner, Rivka; Gilkeson, Robert; Ros, Pablo R.; Gupta, Amit
Abstract : Objective: The aim of this study was to investigate the quantitative and qualitative effects of virtual monoenergetic images (VMI) by spectral detector computed tomography (SDCT) on calcium blooming in coronary computed tomography angiography. Methods: Coronary computed tomography angiography using SDCT was performed on 42 patients with coronary artery calcifications. Stenosis grading by diameter and area of calcified plaques and free lumen using VMI from 70 to 140 keV was performed and compared with measurements by conventional images. In addition, interobserver reliability and subjective image quality were assessed by 2 experienced readers. Results: A total of 61 coronary arteries were evaluated. Stenosis grading by diameter and area showed significant incremental decrease, from 48.86% to 22.82% and from 41.18% to 11.33%, respectively, with increasing VMI ( P < 0.05). Interobserver reliability was excellent (intraclass correlation coefficient >0.99). Overall image quality was best at 80 keV. Conclusions: Calcium blooming significantly decreases at higher monoenergetic levels from SDCT, increasing luminal dimensions and decreasing stenotic grading, with best overall subjective image quality using 80-keV VMI.